Emergence of the Gulf of Guinea in the Global Economy : Prospects and Challenges - Ondo Mane, Damian (IMF Working Papers; Working Paper, 2005)
The Gulf of Guinea's tremendous potential is creating investment opportunities for the region. Some of its resources, such as oil, minerals, and forests, continue to attract significant investments whereas others, like natural gas, could be exploited to their full potential if necessary investments were undertaken. Nevertheless, the Gulf of Guinea has to cope with numerous challenges, both exogenous and endogenous, before it can fully benefit from its riches. One of these problems stems from the overwhelmingly weak institutions and governance, pointed by stylized facts, which add to the risks of "natural resource curse" and can feed the theory of the "Paradox of Plenty." The case is made that regional institutional arrangements and increased involvement of the international community and the African Diaspora should complement the efforts in which countries in the region should engage to address policy and governance issues. Complementary avenues are proposed, including maintaining stability and security, making better use of the region's own assets, putting in place a favorable business environment, and augmenting exports with value addition.